La culture et la production de l'aliment miracle : La spiruline - Gherib Ismahen; ouslati Yassamine (My University, 2022)
Well-known as Spirulina, Arthrospira platensis is a filamentous cyanobacterium, or blue algae, that readily reproduce in alkaline lakes and steaming waters around the world. In our work, we have cultivated Spirulina in the laboratory in a climate different from the preferred one, the progression of growth for more than a month is monitored taking into account the climatic and physic-chemical factors which act directly on their growth. After the experiments carried out in the laboratory, it has been shown that the culture of Spirulina depends on the temperature and the pH as well as on the illumination, It is therefore necessary to take care to maintain a temperature above 25°C and sufficient light for photosynthesis and a pH between 9 and 10 thus providing it with these nutrient needs which allowed us to obtain 01gr/l of fresh biomass. -------------------------------------------------------------------------------------------------------------------------------------------- تعرف باسم سبيرولينا (Arthrospira Platensis) , وهي بكتيريا زرقاء خيطية, أو طحالب زرقاء ,تتكاثر بسهولة في البحيرات القلوية والمياه البخارية حول العالم. في عملنا، قمنا بزراعة سبيرولينا في المختبر في مناخ مختلف عن المناخ المفضل لها ، تم مراقبة تقدم النمو لأكثر من شهر مع مراعاة العوامل المناخية, الفيزيائية و الكيميائية التي تؤثر بشكل مباشر على نموها. بعد التجارب التي أجريت في المختبر، تبين أن استزراع السبيرولينا يعتمد على درجة الحرارة ودرجة الحموضة وكذلك على الإضاءة، لذلك من الضروري الحرص على درجة الحرارة أعلى من 25 درجة مئوية وإضاءة كافية لعملية التمثيل الضوئي وأيضا درجة الحموضة بين 9 و10 وعندما تم تزويدها بهذه الاحتياجات الغذائية, سمحت لنا بالحصول على 01 غرام / لتر من الكتلة الحيوية الطازجة --------------------------------------------------------------------------------------------------------------------------------------------- Bien connu sous le nom de spiruline, Arthrospira Platensis, est une cyanobactérie filamenteuse, ou algue Bleu, qui se reproduit facilement dans les lacs alcalins et les eaux à vapeur du monde entier. Dans notre travail, nous avons cultivée la spiruline au laboratoire dans un climat différent de celui préféré, la progression de la croissance pendant plus d’un mois est surveillée en tenant compte des facteurs climatiques et physico-chimiques qui affectent directement leur croissance. Après les expériences réalisées au laboratoire, il a été démontré que la culture de spiruline dépend de la température et du pH ainsi de l’éclairement, Il faut donc veiller à maintenir une température supérieure à 25°C et une lumière suffisante à la photosynthèse et un pH entre 9 et 10 ainsi de lui fournir ces besoins en nutriments ce qui nous a permis d’obtenir 01gr/l de biomasse fraiche.